PENGARUH KERJASAMA INDONESIAN-JAPAN ECONOMIC PARTNERSHIP AGREEMENT (IJEPA) TERHADAP DOMINASI ASTRA HONDA MOTOR (AHM) DI INDONESIA - Sinaga, Rudi; Jamaan, Ahmad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
Indonesian-Japan Economic Partnership (IJEPA) is a trade and investment cooperation agreement that provides an opportunity to conduct export-import trade between Indonesia and Japan with low tariffs based on free trade. Japanese investment in Indonesia is generally in the manufacturing sector, Especially in the automotive and electronics industries. One form of the cooperation carried out by Indonesia within the IJEPA framework in the automotive sector is to form trade relations with PT. Astra International by establishing a two-wheeled vehicle assembly company under the name PT. Astra Honda Motor. Within the IJEPA framework, Indonesia provides the USDFS tariff scheme for Japan and Japan provides the MIDEC program for Indonesia. Therefore, the researcher drew the question